Possible Ceres bow shock surfaces based on fluid models. Issue 5 (3rd May 2017) - Jia, Y.‐D.; Villarreal, M. N.; Russell, C. T.
Abstract: The hot electron beams that Dawn detected at Ceres can be explained by fast‐Fermi acceleration at a temporary bow shock. A shock forms when the solar wind encounters a temporary atmosphere, similar to a cometary coma. We use a magnetohydrodynamic model to quantitatively reproduce the 3‐D shock surface at Ceres and deduce the atmosphere characteristics that are required to create such a shock. Our most simple model requires about 1.8 kg/s, or 6 × 10 25 /s water vapor production rate to form such a shock. Such an estimate relies on characteristics of the solar wind‐Ceres interaction. We present several case studies to show how these conditions affect our estimate. In addition, we contrast these cases with the smaller and narrower shock caused by a subsurface induction. Our multifluid model reveals the asymmetry introduced by the large gyroradius of the heavy pickup ions and further constrains the IMF direction during the events. Plain Language Summary: This study estimates detailed parameters of the Ceres bow shock inferred by energetic electron beams arriving at Dawn. We present results using a single‐fluid MHD model and a multifluid MHD model to show how the interaction conditions affect the shock formation. While observation favors global exosphere with no significant body induction, we found that a shock requires a gas production rate above 1.8 kg/s at Ceres. Key Points: We estimate detailed parameters of the Ceres bow shock inferred by energetic electron beams observed by Dawn We use a single‐fluid MHD model and a multifluid plasma model to show how interaction conditions affect the shock formation Occurrence of a shock requires a gas production rate above 1.8 kg/s at Ceres